CONTENT, FORM, METHOD AND MEANS OF TEACHING "INFORMATICS AND INFORMATION TECHNOLOGIES" USING MEDIA TECHNOLOGIES (World Bulletin of Management and Law, 2022)
Organization of the teaching process of informatics and information technologies on the basis of media technologies is presented
Keywords: Media technology; media education; resource; form